Information requirements for earthquake damage assessment of structural walls. Issue 1 (January 2016) - Anil, Engin Burak; Akinci, Burcu; Garrett, James H.; Kurc, Ozgur
Abstract: The engineering analysis for determining the remaining seismic capacity of buildings following earthquakes requires performing structural calculations, observations of the actual damage, and applying extensive engineering judgment. Additionally, the analysis should often be performed under stringent time requirements. This study identifies the information requirements for representing the damage information and performing the visual damage assessment of structural walls. The damage descriptions for seven common damage modes of structural walls were studied by employing the affinity diagramming method. The study showed that the information required to represent the damaged conditions can be grouped under five broad categories and using seventeen damage parameters. A sensitivity analysis showed that the damage parameters have varying degrees of importance. The results of the study can be used to develop formal representation of damage information in information models and potentially allow better allocation of data collection time in the field.